Success factor of KAPF training program conducted by MFA during October 2010 / Nadirah Md.Nor - Md.Nor, Nadirah (Faculty of Business and Management, 2011)
The research entitled “Success Factor of KAPF Training Program Conducted by MFA during October 2010” is conducted with three objectives which are first to identify what is the level of successful training conducted by MFA during month of October 2010, second is to identify what are the relationship between training success and each of independent variable and third is to determine most influence factors towards the success factor of KAPF training program conducted by MFA during October 2010. The respondents of this study are the participants who came for training conducted by MFA during October 2010. 60 questionnaires were distributed in order to complete the purpose of study. The researcher used census, while telephone interview and email interview were used as the method of collecting data. At the end of the researcher found the level of training to be positive, with each of the factors mentioned as the independent variables having positive results towards the successful training conducted by MFA during October 2010.